Effects of Graphene Oxide and Oxidized Carbon Nanotubes on the Cellular Division, Microstructure, Uptake, Oxidative Stress, and Metabolic Profiles - Hu, Xiangang; Ouyang, Shaohu; Mu, Li; An, Jing; Zhou, Qixing (Environmental science & technology, 2015)
Nanomaterial oxides are common formations of nanomaterials in the natural environment. Herein, the nanotoxicology of typical graphene oxide (GO) and carboxyl single-walled carbon nanotubes (C-SWCNT) was compared. The results showed that cell division of Chlorella vulgaris was promoted at 24 h and then inhibited at 96 h after nanomaterial exposure. At 96 h, GO and C-SWCNT inhibited the rates of cell division by 0.08–15% and 0.8–28.3%, respectively. Both GO and C-SWCNT covered the cell surface, but the uptake percentage of C-SWCNT was 2-fold higher than that of GO. C-SWCNT induced stronger plasmolysis and mitochondrial membrane potential loss and decreased the cell viability to a greater extent than GO. Moreover, C-SWCNT-exposed cells exhibited more starch grains and lysosome formation and higher reactive oxygen species (ROS) levels than GO-exposed cells. Metabolomics analysis revealed significant differences in the metabolic profiles among the control, C-SWCNT and GO groups. The metabolisms of alkanes, lysine, octadecadienoic acid and valine was associated with ROS and could be considered as new biomarkers of ROS. The nanotoxicological mechanisms involved the inhibition of fatty acid, amino acid and small molecule acid metabolisms. These findings provide new insights into the effects of GO and C-SWCNT on cellular responses.